2011
DOI: 10.1590/s0104-11692011000400023
|View full text |Cite
|
Sign up to set email alerts
|

Stressors in nurses working in Intensive Care Units

Abstract: This is a descriptive cross-sectional study. The sample consisted of 235 nurses from two intensive care units in Porto (Portugal). The purpose of this study was to identify stressors for nurses working in intensive care units. The data was collected using the following: i) a questionnaire (for socio-demographic variables, physical aspects of work and variables related to the work context; ii) Interpersonal Work Relations Scale; iii) Nurse Stress Index.Nurses in the early phase of their career have higher stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 8 publications
5
26
0
17
Order By: Relevance
“…The situations involving death and/or disease with an emotionally-negative character constitute one of the stressors most-evidenced by the investigators in widely-differing areas of nursing, although they particularly stand out in the studies on nurses in the area of oncology (6,9,21) . In one study (21) with nurses from different oncological institutions in Sweden, it was observed that the levels of stress varied from low to serious, and the main sources of stress identified Similarly, in one study (22) undertaken with Portuguese nurses in an Intensive Care…”
Section: Discussionmentioning
confidence: 99%
“…The situations involving death and/or disease with an emotionally-negative character constitute one of the stressors most-evidenced by the investigators in widely-differing areas of nursing, although they particularly stand out in the studies on nurses in the area of oncology (6,9,21) . In one study (21) with nurses from different oncological institutions in Sweden, it was observed that the levels of stress varied from low to serious, and the main sources of stress identified Similarly, in one study (22) undertaken with Portuguese nurses in an Intensive Care…”
Section: Discussionmentioning
confidence: 99%
“…8,9,10,11 The stresses related to the hospital environment are cumulative and progressive, and the resulting health problems can be triggered by several factors, including nightshift work on weekends and holidays, the negative psychological impact of witnessing patient suffering, and the psychological characteristics of the healthcare professionals themselves.…”
Section: 7mentioning
confidence: 99%
“…Among our study's participants, the presence of anxiety as a personality trait (IDATE-T) correlated positively with the presence of TMD, confirming its role as an etiological factor of this type of pathology in the temporomandibular joint. 1,2,3,7,8,14,16,19 On the other hand, when Fonseca's questionnaire score and TMD severity were associated with the severity of trait and state anxiety, only state anxiety (IDATE-E) correlated positively with TMD severity, indicating that, once present, the variation in TMD severity is mainly determined by an individual's state of anxiety and not by their personality.…”
mentioning
confidence: 94%
“…The stress might have repercussions that are represented on the level of absenteeism, turnover rate, decrease on the worker's performance, reduced motivation and satisfaction with their work, increase on work accidents and mistakes [17].…”
Section: Discussionmentioning
confidence: 99%